2003
DOI: 10.1161/01.str.0000062346.70983.df
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of −174 G/C Polymorphism of the Interleukin-6 Gene Promoter and 469 E/K Polymorphism of the Intercellular Adhesion Molecule-1 Gene in Italian Patients With History of Ischemic Stroke

Abstract: There is a synergistic effect of IL-6 G/C and ICAM-1 E/K gene polymorphisms in patients with stroke history. Reciprocal interactions between genotypes may contribute in determining the risk profile for cardiovascular diseases and may merit further investigation as potential therapeutic targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 31 publications
6
71
1
3
Order By: Relevance
“…However, epidemiological data on the association of the IL-6 gene polymorphism with ischemic stroke, subtypes and intermediate phenotypes are conflicting. Pola et al [33] observed an increased risk of ischemic stroke in carriers of the IL-6 GG genotype (OR=8.6), which is in agreement with the results of Stefan Greisenegger [34] . Rundek et al also revealed that the G allele confers an increased risk of IMT [35] .…”
Section: Ischemic Strokesupporting
confidence: 80%
“…However, epidemiological data on the association of the IL-6 gene polymorphism with ischemic stroke, subtypes and intermediate phenotypes are conflicting. Pola et al [33] observed an increased risk of ischemic stroke in carriers of the IL-6 GG genotype (OR=8.6), which is in agreement with the results of Stefan Greisenegger [34] . Rundek et al also revealed that the G allele confers an increased risk of IMT [35] .…”
Section: Ischemic Strokesupporting
confidence: 80%
“…21,38 -49 We excluded 1 article published in Chinese; this casecontrol study found the GG genotype to be significantly more frequent in transient ischemic attack patients and to be predictive of subsequent ischemic stroke within 3 months. 49 Three of the remaining 12 articles reported on a subset of patients from a later publication (confirmed by the listed corresponding authors), 41,46,47 leaving 9 unique patient populations (Table). No additional references were found from the bibliographies of the selected articles.…”
Section: Resultsmentioning
confidence: 97%
“…[38][39][40] Although a clear picture of the role of IL-6 in stroke has not yet been elucidated, an increase in IL-6 production following cerebral ischemia has been described in several clinical studies 21,34,41,42 and elevated levels of the IL-6 cytokine have been correlated with severity and clinical outcome of stroke. 28,43,44 Furthermore, polymorphisms of the promoter IL-6 gene have been associated with stroke 45,46 and the IL-6 system has been associated with acute inflammatory response after stroke. 47 In addition, the IL-8 chemokine has also been associated with the recruitment of inflammatory cells and is increased in stroke patients.…”
Section: Resultsmentioning
confidence: 99%